Kepemimpinan Paternal dalam Pewarisan Iman Kristen: Respons terhadap Fatherless dan Disrupsi Digital Berdasarkan Ulangan 6:6–7 - Bega, Yoel; Simanjuntak, Manlian Ronald. A. (Jurnal Apokalupsis, 2025)
The transmission of faith within Christian families faces significant challenges due to the phenomenon of fatherlessness and the disruptive impact of the digital era, which reshape relational patterns and the formation of children’s identity. Although previous studies have addressed fatherlessness and digital influence separately, limited research integrates these issues within a coherent theological framework grounded in Deuteronomy 6:6–7. This article aims to analyze presence-based paternal leadership as a theological response to the crisis of faith transmission in the context of Indonesian Christian families. The study employs a qualitative approach through library research, incorporating textual and lexical analysis of the Hebrew terms shanan (intentional sharpening) and dabar (relational dialogue), alongside scholarly discussions on fatherlessness, patriarchy, and digital disruption. The findings indicate that faith transmission requires three essential dimensions: intentionality, relationality, and active presence throughout the rhythms of daily family life. The crises of fatherlessness and digital dominance reflect the weakening of these dimensions. This study proposes a reconstruction of paternal leadership as presence-based leadership that integrates authority, responsibility, and relational engagement in managing family life, including digital spaces. The novelty of this research lies in its theological synthesis of Deuteronomy 6:6–7 with fatherlessness and digital disruption within the Indonesian patriarchal context.